Fabrication of Compliant EP-FG Composite Automobile Shell Structure using Compression Moulding Process - K. Balakrshnan, Vikneshwaran (2018)
Corrugations are believed to enhance the mechanical properties of a shell structure. In this study, the theory of corrugation is applied to enhance the flexibility of epoxy-fiberglass material which is being used widely in automotive industry. This could fulfill the requirement of using a flexible composite material for automobile shell structure for a more crashworthy design. Two different corrugated profiles were studied in this project which are the damped curve and pyramidal groove profiles. Rubber moulds were fabricated and used for the corrugated epoxy-fiberglass composite preparation. A compression moulding machine was used to form the corrugations on the composite material as it can deliver high pressure and temperature to cure the laminate. In this study, the compression moulding process was carried out under constant parameters: temperature, pressure and holding time. Results obtained from the tensile test of the corrugated epoxy-fiberglass composite sheets were compared with the tensile properties of a flat epoxy-fiberglass composite sheet to determine the effect of corrugations in terms of flexibility. The pyramidal groove corrugation managed to enhance the flexibility of the epoxy-fiberglass composite sheet, however there was a significant decrease in yield load, and no notable changes in tensile strength, yield strength and elongation. On the other hand, the flexibility achieved by the sample with damped curve corrugation is higher than the flat sample, but lower than the flexibility possessed by the pyramidal groove sample. Elongation of the damped curve sample prior to fracture is two times higher compared to the elongation achieved by both pyramidal groove and flat samples. In conclusion, the epoxy-fiberglass composite sheet with the damped curve corrugation profile is the best, as it exhibits the desired increase in flexibility with minimal loss in terms of tensile strength, yield load and yield strength.